Epidemiology of Pediatric-Onset Multiple Sclerosis: A Systematic Review of the Literature. (October 2019) - Jeong, Anna; Oleske, Denise M.; Holman, Joan
Multiple sclerosis onset in youth is increasingly recognized. A systematic review was conducted to assess incidence and prevalence of pediatric-onset multiple sclerosis, focusing on occurrence by age subgroups and disease course. A literature search for the period 1965-2018 was carried out, selecting population-based studies of multiple sclerosis in individuals aged 19 years and younger. Nineteen studies met inclusion criteria. One pediatric neurologist extracted the data. Overall incidence ranged from 0.05 (95% confidence interval 0.03-0.08) to 2.85 (95% confidence interval 2.83-2.86) per 100 000 children and overall prevalence from 0.69 (95% confidence interval 0.58-0.80) to 26.92 (95% confidence interval 26.61-27.23) per 100 000 children. Incidence increased with age. The female-male ratio increased from 1.2:1 in children <12 years old to 2.8:1 in children ≥12 years old. Ten studies (n=521 children) reported disease course. Seven studies found only relapsing-remitting disease and 3 studies found primary-progressive disease in 3.0% to 6.7%. Two secondary-progressive disease cases were identified. Epidemiologic data aid in understanding the magnitude of multiple sclerosis and its clinical phenotypes, for planning for new disease-modifying therapies in the pediatric population.